Figure 8 in A further study on littoral ciliates (Protozoa, Ciliophora) near King George Island, Antarctica, with description of a new genus and seven new species - Wilbert, Norbert; Song, Weibo (Zenodo, 2008)
Figure 8. Urotricha antarctica nov. spec. (A–F), Pleuronema coronatum (G–I) and Pseudocohnilembus persalinus (J–N) after protargol (A–I, K) and silver-nitrate (J, L–N) impregnations. (A) Apical view, to show the oral area, arrowheads mark the tiny extrusomes in the roomy cytostome, arrow indicates the moral kinety. (B, C) Anterior portion, arrows mark the dorsal brush, while double-arrowheads in C indicate the macronucleus. (D, E) Caudal area, arrows mark the caudal cilia. (F) Caudal view, arrow indicates the contractilevacuole pores. (G, I) Ventral view, to show the buccal apparatus. (H) The same specimen as in G, to show the shortened preoral kineties (arrowheads). (J) Anterior part, to show the ciliafree apical area (arrowhead). (K) Right lateral view, to show the somatic (arrowhead) and buccal (arrow) ciliature. (L) Right view, to show the contractile-vacuole pore (arrow). (M) Ventral view, to show the cytopyge (arrow) and contractile-vacuole pore (arrowhead). (N) Ventral view, to shouw the silverline structure (arrow) conecting the membranelles (arrowheads). Scale bars: 30 Mm. : Published as part of Wilbert, Norbert & Song, Weibo, 2008, A further study on littoral ciliates (Protozoa, Ciliophora) near King George Island, Antarctica, with description of a new genus and seven new species, pp. 979-1012 in Journal of Natural History 42 (13-14) on page 1004, DOI: 10.1080/00222930701877540, http://zenodo.org/record/5219160